Psychoeducation Psychological Well Being dan Kenakalan Remaja - Sari, Ika Novita (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2017)
Abstract This study aims to determine whether psychoeducation psychological well being can reduce juvenile delinquency in terms of gender. This research is included in the type of experimental research. The design used is quasi experimental control group pretest-posttest design. Subjects in this study consisted of 20 people as an experimental group and 20 people as a control group. Data collection instruments use juvenile delinquency scales. Analysis of data using the non-parametric Wilcoxon Sign Rank obtained an average post test score of the experimental group was lower than the average post test score in the control group with a significance of p = 0.000 (p <0.05). This means that there is the influence of psychoeducation psychological well being on juvenile delinquency. Based on the Man Whitney U test test obtained Z = -1243 with p = 0214 (p> 0.05), which means there is no difference in the decrease in juvenile delinquency between men and women. Keywords: psychoeducation psychological well being, juvenile delinquency